2022
DOI: 10.3389/fpls.2022.1085409
|View full text |Cite
|
Sign up to set email alerts
|

Responses of root system architecture to water stress at multiple levels: A meta-analysis of trials under controlled conditions

Abstract: Plants are exposed to increasingly severe drought events and roots play vital roles in maintaining plant survival, growth, and reproduction. A large body of literature has investigated the adaptive responses of root traits in various plants to water stress and these studies have been reviewed in certain groups of plant species at a certain scale. Nevertheless, these responses have not been synthesized at multiple levels. This paper screened over 2000 literatures for studies of typical root traits including roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 174 publications
1
20
1
Order By: Relevance
“…When under stress, plants generally maintain a high root–shoot ratio in order to allow higher resource allocation toward roots for enhanced water and nutrient absorption (Kou et al., 2022). Roots are the most crucial part that helps plants adapt better in a water‐limited environment by maintaining plant fitness.…”
Section: Root and Its Rolementioning
confidence: 99%
See 2 more Smart Citations
“…When under stress, plants generally maintain a high root–shoot ratio in order to allow higher resource allocation toward roots for enhanced water and nutrient absorption (Kou et al., 2022). Roots are the most crucial part that helps plants adapt better in a water‐limited environment by maintaining plant fitness.…”
Section: Root and Its Rolementioning
confidence: 99%
“…Acquisition of resources from soil is largely dependent on the architecture of the root, and any changes in this architecture significantly affect resource capture efficiency in plants (Morris et al., 2017). RSA is defined as the spatial configuration of roots that help plants anchor and forage for nutrients and water in soil domains (Kou et al., 2022). RSA is determined by a variety of root traits such as root angle, root‐to‐shoot ratio, root length, root hair, root diameter, root biomass, and root tip (Siddiqui et al., 2021).…”
Section: Root System Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that response of RSA to drought varies considerably at intra-and interspecies level (Kou et al, 2022). Ability of plant to survive and maintain its yield under water scarce conditions is regarded as the plant plasticity response which confers drought tolerance to it (Gao et al, 2015;Suseela et al, 2020).…”
Section: Relation Of Rsa With Droughtmentioning
confidence: 99%
“…It has been proposed that root traits helps in reducing the root system cost (including greater formation of aerenchyma, smaller root diameter, reduced area of living tissue, increased size of cortical cell, fewer nodal roots, root cortical senescence) and aid in promoting elongation of roots, hence increased capture of resources and deeper exploration of soil (Lynch 2013;Fonta et al, 2022). Steeper angle of root growth is known to improve drought tolerance, for example, in rice, deeper rooting 1 (dro1 ) gene which is responsible for influencing angle of root growth has been used in breeding programs and cloning experiments extensively (Uga et al 2013;Kitomi et al 2015;Kou et al, 2022). The number and size of metaxylem also affects drought tolerance and water use efficiency in plants.…”
Section: Relation Of Rsa With Droughtmentioning
confidence: 99%